Psychological and biological foundations of time preference: Evidence from a day reconstruction study with biological tracking - Michael Daly; Liam Delaney; Colm Harmon (University College Dublin, UCD School of Economics, 2008)
This paper considers the relationship between the economic concept of time preference and relevant concepts from psychology and biology. Using novel data from a time diary study conducted in Ireland that combined detailed psychometric testing with medical testing and real-time bio-tracking, we examine the distribution of a number of psychometric measures linked to the economic concept of time preferences and test the extent to which these measures form coherent clusters and the degree to which these clusters are related to underlying biological substrates. The paper finds that financial discounting is related to a range of psychological variables including consideration of future consequences, self-control, conscientiousness, extraversion, and experiential avoidance as well as being predicted by heart rate variability and blood pressure.
hdl:10197/593
Keywords: 330